2001
DOI: 10.1002/1099-0690(200105)2001:10<1927::aid-ejoc1917>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile and Convenient Method for the Functionalization of Porphyrins

Abstract: The condensation of 3‐(chloromethyl)benzoyl chloride with different atropisomers of meso‐(tetra‐o‐aminophenyl)porphyrin (TAPP), followed by the reaction of a series of nucleophilic reagents leads, among others, to precursors of biomimetic models of heme proteins such as cytochrome c oxidase (CcO). This synthesis can also be applied as an efficient two‐step reaction to obtain highly functionalized porphyrin derivatives potentially useful for cation binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 32 publications
(23 reference statements)
0
30
0
Order By: Relevance
“…To do so, we designed a series of ligands with preorganized straps allowing ester or carboxylic acid groups to hang above the N-core, with a possible chelate effect. Such structures were obtained by reacting diethyl malonate on several atropisomers (aaaa, abab, and aabb) of picket porphyrins [28,29]. The two ligands 3 and 4 bearing ester groups in their straps in the aabb and abab series have been first investigated for bismuth complexation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To do so, we designed a series of ligands with preorganized straps allowing ester or carboxylic acid groups to hang above the N-core, with a possible chelate effect. Such structures were obtained by reacting diethyl malonate on several atropisomers (aaaa, abab, and aabb) of picket porphyrins [28,29]. The two ligands 3 and 4 bearing ester groups in their straps in the aabb and abab series have been first investigated for bismuth complexation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using proton NMR spectroscopy, we have been able to demonstrate the effective coordination of the nitrogen base to the metal in the porphyrin. For instance, by preparing the zinc complex of a porphyrin bearing the tailed 2-methylimidazole and by comparison with the chemical shifts of the free-base compound, the signals corresponding to the 2-methylimidazole are clearly downfield-shifted [16].…”
Section: Resultsmentioning
confidence: 99%
“…This second approach is based on a general and easy preparation of several types of strapped porphyrins in only two steps, starting from different 'U-shaped' acceptors, by acylation of three isomers of TAPP [22]. This methodology was shown particularly adapted to the preparation of various cation binding superstructures and can be regarded as a generalization of Chang's ligand appended reaction [23].…”
Section: Bis-strapped Porphyrinsmentioning
confidence: 99%
“…First, the two signals of H 7 are really different, one of them being strongly downfield-shifted to 6.97 ppm. This value compares well with the chemical shift of the same proton of the analogous free base porphyrin in the aaaa geometry for which the X-ray structure clearly showed that the two straps, located on the same side of the porphyrin and because of a reciprocal steric repulsion, were almost in vertical position [22]. Second, one doublet of the AB system corresponding to the benzylic protons is shielded down to À0.06 ppm, just like in 15Zn (Figure 9.11d).…”
Section: Bis-strapped Porphyrinsmentioning
confidence: 99%